LTR retrotransposon landscape in Medicago truncatula: more rapid removal than in rice - Liu Jin-Song; Wang Hao (BMC Genomics, 2008)
Abstract Background Long terminal repeat retrotransposons (LTR elements) are ubiquitous Eukaryotic TEs that transpose through RNA intermediates. Accounting for significant proportion of many plant genomes, LTR elements have been well established as one of the major forces underlying the evolution of plant genome size, structure and function. The accessibility of more than 40% of genomic sequences of the model legume Medicago truncatula (Mt) has made the comprehensive study of its LTR elements possible. Results We use a newly developed tool LTR_FINDER to identify LTR retrotransposons in the Mt genome and detect 526 full-length elements as well as a great number of copies related to them. These elements constitute about 9.6% of currently available genomic sequences. They are classified into 85 families of which 64 are reported for the first time. The majority of the LTR retrotransposons belong to either Copia or Gypsy superfamily and the others are categorized as TRIMs or LARDs by their length. We find that the copy-number of Copia-like families is 3 times more than that of Gypsy-like ones but the latter contribute more to the genome. The analysis of PBS and protein-coding domain structure of the LTR families reveals that they tend to use only 4–5 types of tRNAs and many families have quite conservative ORFs besides known TE domains. For several important families, we describe in detail their abundance, conservation, insertion time and structure. We investigate the amplification-deletion pattern of the elements and find that the detectable full-length elements are relatively young and most of them were inserted within the last 0.52 MY. We also estimate that more than ten million bp of the Mt genomic sequences have been removed by the deletion of LTR elements and the removal of the full-length structures in Mt has been more rapid than in rice. Conclusion This report is the first comprehensive description and analysis of LTR retrotransposons in the Mt genome. Many important novel LTR families were discovered and their evolution is elucidated. Our results may outline the LTR retrotransposon landscape of the model legume.